Syndesmotic Loose Bodies in Trimalleolar Ankle Fractures - Hernan E Coria; Emanuel Fedun Rodriguez; Daniel Sartorelli (Journal of Foot and Ankle Surgery (Asia Pacific))
Introduction: Trimalleolar ankle fractures have a worse prognosis than other ankle fractures and are in most cases associated with other injuries. Adequate reduction is the key to restoring ankle function. Four percent of the syndesmosis may remain unstable due to poor reduction or interposed structures. The objective of this paper is to study the incidence and epidemiology of syndesmotic loose bodies in trimalleolar ankle fractures. Materials and methods: Thirty-nine trimalleolar ankle fractures were retrospectively studied. Radiographs and computed tomography (CT) were performed. Fractures were classified according to Weber/Arbeitsgemeinschaft für Osteosynthesefragen (AO), and posterior malleolar fractures were classified according to Haraguchi and Bartoníček/Rammelt. Inclusion criteria: Adult patients with acute trimalleolar ankle fractures treated by the same surgical team were included. Pathological fractures and patients treated by another team were excluded. Age, sex, laterality, and the presence of loose syndesmotic bodies were documented. Student's t-test and Chi-squared tests were performed to analyze the statistical relationship between the studied variables. Results: Seven patients were men and 32 were women, with a mean age of 60 years (range 25–98 years). We found 33 B3 fractures (45%) of which were associated with loose bodies. There were only six C2 fractures, and two of them were associated with loose bodies (33%) (p = 0.0004). There were significant differences in the distribution by sex for the presence of syndesmotic loose bodies. The incidence is 57% for males and 41% for females. No association between loose bodies and Haraguchi or Bartoníček/Rammelt types was found. All loose bodies were visible on CT, and only two cases on X-ray. Conclusion: The incidence of loose bodies in the series studied is 43.5%. Syndesmotic loose bodies are statistically associated with B3 fractures. The statistical incidence is higher in men. Performing CT scans on all trimalleolar fractures is mandatory. Level of evidence—IV.